The Observed Longitudinal Relationship between Future Orientation and Substance Use Among a Cohort of Youth with Serious Criminal Offenses. (15th October 2018) - Brooks, Merrian; Miller, Elizabeth; Abebe, Kaleab; Mulvey, Edward
Abstract: Background : Future orientation (FO), an essential construct in youth development, encompassing goals, expectations for life, and ability to plan for the future. This study uses a multidimensional measure of future orientation to assess the relationship between change in future orientation and change in substance use over time. Methods : Data were from the Pathways to Desistence study. Justice involved youth (n = 1, 354), ages 14 to 18 at time of recruitment, completed interviews every six months for three years. Multiple measures were chosen a priori as elements of future orientation. After evaluating the psychometrics of a new measure for future orientation, we ran mixed effects cross-lagged panel models to assess the relationship between changes in future orientation and substance use (tobacco, marijuana, hard drugs, and alcohol). Results : There was a significant bidirectional relationship between future orientation and all substance use outcomes. Adjusted models accounted for different sites, sex, age, ethnicity, parental education, and proportion of time spent in a facility. In adjusted models, higher levels of future orientation resulted in smaller increases in substance use at future time points. Conclusions : Future orientation and substance use influence each other in this sample of adolescent offenders. Treating substance use disorders is also likely to increase future orientation, promoting positive youth development more generally. This study expands our understanding of the longitudinal relationship between changes in future orientation and changes in levels of substance use in a sample of justice involved youth with high levels of substance use, a group of considerable clinical and policy interest.